The "Cosmic" Task of the Youngest Children: Direct, Anticipate, or Respect? Experiences Working with Small Children - Honegger Fresco, Grazia (Journal of Montessori Research, 2024)
The article derived from Grazia Honegger Fresco’s years in close cooperation with Maria Montessori and Adele Costa Gnocchi. The author illustrates how small children from the moment they start using their hands and are standing unassisted on their own legs must act in their own way. The teacher must observe before acting and intervene as little as possible. Honegger Fresco follows the work of Montessori and Costa Gnocchi and she compares the findings with different fields of science, such as ethnology and neurology. As a result of her observations and experiences she points toward the relationship between a good childhood, and in the long term, human responsibility on Earth, using the concept “the Cosmic Task”.The method in this article is based on autoethnography, as the author shares her personal experience and reflections, both as a teacher and as an educator. The aim is to shed light on aspects regarding the needs of small children and to point at the essential role of adults, educators as well as parents. As Schiedi explains, autoethnography “extends its narrative horizon to a social, professional, organizational dimension of the self ” (2016). During Honegger Fresco’s career, she was primarily inspired by Maria Montessori’s research about child development and children’s needs and rights, and she had continuously deepened her understanding by studying other researchers in this field. Thus, the article will share her conviction that by serving the creative spirit of the youngest children we will build a better future for our planet.